2018
DOI: 10.1007/s00420-018-1390-8
|View full text |Cite
|
Sign up to set email alerts
|

Sick leave before and after a work-place targeted terror attack

Abstract: ObjectivesTo estimate the rate of sick leave and sick leave diagnosis among employees before and after a work-place targeted terror attack, and to compare sick leave in subgroups of employees based on gender and trauma exposure.MethodsData on sick leave and diagnosis in ministerial employees from the period 3 years before to 3 years after the 2011 bombing in the governmental district of Oslo was retrieved from the Norwegian Social Insurance Administration Registries.ResultsPrior to the attack, sick leave was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…Participants with sick leave did not differ significantly from participants without sick leave on several relevant background variables; one exception was a larger proportion of women in the former group. This is in line with previous research where the terrorist attack had a larger negative impact on the work ability of women 7. The PTSD symptoms were also higher among participants with sick leave.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Participants with sick leave did not differ significantly from participants without sick leave on several relevant background variables; one exception was a larger proportion of women in the former group. This is in line with previous research where the terrorist attack had a larger negative impact on the work ability of women 7. The PTSD symptoms were also higher among participants with sick leave.…”
Section: Discussionsupporting
confidence: 92%
“…For the purpose of this study, we used survey data on employees’ health and PTSD symptoms, background variables and information on psychosocial work environment from 10 months after the attack, linked with registry data on doctor-certified sick leave for the period of 12–24 months after the attack. Since the first years after the attack were most prominent for sick leave risk and PTSD, we focused on this especially sensitive period 7. In this study population (n=1649), we identified 94 participants eligible for this study, all fulfilling the PTSD symptom criteria and with relevant data on doctor-certified sick leave.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study of people exposed to the September 11, 2001 attacks in New York showed no statistical significant association between exposure and sickness absence due to psychological or physical symptoms [18]. However, a study of ministerial employees in Norway who were exposed to the 22nd of July, 2011 Oslo bombing showed an increase in sickness absence rates over a two-year period after the attack compared to before the attack [19]. Thus, there is limited evidence of an association between exposure to workplace terrorism and subsequent sickness absence.…”
Section: Workplace Terrorism and Sickness Absencementioning
confidence: 99%